2022
DOI: 10.3389/fmicb.2022.879674
|View full text |Cite
|
Sign up to set email alerts
|

Two New Sulfate-Modified Dibenzopyrones With Anti-foodborne Bacteria Activity From Sponge-Derived Fungus Alternaria sp. SCSIOS02F49

Abstract: At present, foodborne diseases (FBDs) caused by bacteria are gradually increasing every year, and the development of new antibiotics is an urgent necessity for human beings. To find novel antibacterial compounds, three sponge-derived fungal strains (SCSIOS02F40, F46, and F49) were investigated. As a result, Alternaria sp. SCSIOS02F49 was selected for investigation on its secondary metabolites because its ethyl acetate (EtOAc) extract of potato dextrose broth (PDB) culture showed rich metabolites and strong ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…121 Albifimbria verrucaria was the source of a modified γ-lactone 272 (ref. 122) and the genus Alternaria yielded a range of metabolites including the meroterpenoids tricycloalternarenes O–R, 273 – 276 , 123 dibenzo-α-pyrone derivatives 277 – 279 , 124 sulfated dibenzopyrones 280 and 281 , 125 phomalone derivatives 282 – 284 (ref. 126) and perylenequinone derivatives 285–287 .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…121 Albifimbria verrucaria was the source of a modified γ-lactone 272 (ref. 122) and the genus Alternaria yielded a range of metabolites including the meroterpenoids tricycloalternarenes O–R, 273 – 276 , 123 dibenzo-α-pyrone derivatives 277 – 279 , 124 sulfated dibenzopyrones 280 and 281 , 125 phomalone derivatives 282 – 284 (ref. 126) and perylenequinone derivatives 285–287 .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…SCSIOS02F49 (Figure 1A, 50-51). Among them, alterlactone 5′-O-sulfate was shown to alter the external structure of S. aureus and caused the rupture or deformation of the cell membranes (Chen et al, 2022b). In addition, Ding et al found three new polyketides, nipyrones A-C (Figure 1A, 52-54), from a marine sponge-associated Aspergillus niger, but only nipyrone C inhibited S. aureus and B. subtilis with MIC values of 8 mg/mL and 16 mg/mL, respectively (Ding et al, 2019).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The mycotoxins in Alternaria sp. had been widely studied, leading to the definition of a series of secondary metabolites, including polyketones ( Lu et al, 2021 ), dibenzopyrones ( Chen et al, 2022 ), anthraquinones ( Chen et al, 2014 ) and cephalochromin ( Song et al, 2021 ). These metabolites have cytotoxic, antiviral and enzyme inhibitory activities ( Xu et al, 2019 ; Tan et al, 2020 ; Saxena, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%